2021
DOI: 10.1002/qre.2962
|View full text |Cite
|
Sign up to set email alerts
|

Control charts in financial applications: An overview

Abstract: Statistical process control (SPC) methods have been widely popular not only in industrial applications but also in recent years in several nonindustrial scientific areas. The basic tools of SPC are control charts. SPC methods have been applied to various financial applications such as portfolio surveillance, stock trading, and interest rates. The purpose of this paper is to present the main applications of statistical monitoring process methods, specifically control charts, to the financial area. We focus on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…In industrial production processes, statistical process control (SPC) offers a variety of control charts for tracking abrupt changes in parameters of quality characteristics [1]. This method is commonly employed, notably in the service, chemical industries, and manufacturing sectors to keep quality tabs on production or manufacturing operations [2].…”
Section: Introductionmentioning
confidence: 99%
“…In industrial production processes, statistical process control (SPC) offers a variety of control charts for tracking abrupt changes in parameters of quality characteristics [1]. This method is commonly employed, notably in the service, chemical industries, and manufacturing sectors to keep quality tabs on production or manufacturing operations [2].…”
Section: Introductionmentioning
confidence: 99%
“…As a different application, control charts have been widely implemented in different areas of the economic and financial market monitoring (this area of study is sometimes referred to as financial surveillance). Bisiotis, Psarakis [ 9 ] have provided a comprehensive review of this subject in which some general categories could be found. One major category is about monitoring of the portfolio weights with the aid of control charts.…”
Section: Introductionmentioning
confidence: 99%
“…These charts are also widely used in several nonindustrial scientific areas including the financial areas. 3 The statistical control charts can generally be classified into two phases: Phase-I and Phase-II. 1,4 First, in Phase-I monitoring, we establish reliable control limits with a clean set of process data and in Phase-II analysis, we use the control limits obtained in Phase-I in the monitoring of a process by comparing the statistic for each successive subgroup as future observations are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Since their introduction by Shewhart, 2 variable control charts, such as the Shewhart control chart, have been extensively adopted to detect if a process is in a state of control in different fields including industrial manufacturing, service sectors, and healthcare systems, to name just a few. These charts are also widely used in several nonindustrial scientific areas including the financial areas 3 …”
Section: Introductionmentioning
confidence: 99%